Realizing The Meaningfulness of Orphanage Youth Life - Riem Malini Pane (Jurnal Penelitian Pendidikan, 2023)
This research contains an analysis of the meaningfulness of life for adolescents living in orphanages. The meaning of life is obtained based on the results of observations and interviews with adolescents at the Hayat Orphanage in Padangsidimpuan City. According to the theory, the adolescents studied in this study are late-stage adolescents. The steps in this study are collecting data through observation and interview techniques, identifying and classifying problems, analyzing the data, offering solutions, and then drawing conclusions. The results of this study are useful as guidelines for providing services and assistance to develop meaningful lives for adolescents in orphanages.